Volatile Memory: Nanostructured Fused Pyrrole Thin Films: Encoding Nano "Bits" with Temporary Remanence (Adv. Electron. Mater. 8/2018). (9th August 2018) - Canjeevaram Balasubramanyam, Ram Kumar; Kandjani, Ahmad E.; Jones, Lathe A.; Periasamy, Selvakannan R.; Wong, Sherman; Narayan, Ramanuj; Bhargava, Suresh K.; Ippolito, Samuel J.; Basak, Pratyay
Abstract : The study showcases a fused pyrrole derivative with volatile memory characteristics as a potential nanoscale data storage medium. The results presented by Samuel J. Ippolito, Pratyay Basak, and co‐workers in article number1700626, are expected to provide key insights towards developing next‐generation high‐density data storage devices that are flexible, affordable, and possess a low‐power consumption.